Rapid Analytical Method Development and Validation for the Simultaneous Estimation of 5-Fluorouracil and Cannabidiol in Plasma and Lipid-based Nanoformulations - Hasan, Nazeer; Imran, Mohammad; Jain, Dhara; Shamim, Athar; Beg, Sarwar; Kesharwani, Prashant; Jain, Gaurav; Ahmad, Farhan J. (Current Analytical Chemistry, 2022)
Background: 5-Fluorouracil (5-FU) is a well-established anticancer drug. Several studies have also demonstrated the anticancer potential of Cannabidiol (CBD) against various malignancies, including skin cancer. Reported synergistic effects of this combination fascinate researchers to consider this for the management of skin cancer. Methods: A simple and robust HPLC method for simultaneous estimation of 5-FU and CBD at its single wavelength (237 nm) was developed and validated. The separation of these compounds was performed on Waters® HPLC system with Hypersil™ C18 RP-column using methanol and water in gradient flow as mobile phase. The method could effectively quantify the nanogram levels of both analytes simultaneously in plasma spiked samples and various nanoformulations. The analytical performance of the proposed method was validated in terms of various parameters, such as linearity, ruggedness, specificity, and few others. Results: 5-FU as well as CBD were successfully detected at 237 nm with retention time of 1.4 and 1.84 minutes, respectively. Calibration curves were found to be linear with R2 values of 0.985 and 0.984 for 5-FU and CBD, respectively. The method was linear, precise, specific and robust. Additionally, prepared method successfully determined concentration of both drugs in combitorial nanoformulations. Conclusion: The findings show that the developed method is simple, reliable, sensitive and economical. It could be employed for the simultaneous estimation of 5-FU and CBD in various in vitro and in vivo studies.
Keywords: HPLC